Design and implementation of an automatic pressure-control system for a mobile sprayer for greenhouse applications - Gonzalez, R.; Pawlowski, A.; Rodriguez, C.; Guzman, J. L.; Sanchez-Hermosilla, J. (Spanish Journal of Agricultural Research, 2012)
This article presents the design and development of an embedded automatic pressure-control system for a mobile sprayer working in greenhouses. The pressure system is mounted on a commercial vehicle, it is composed of two on/off electrovalves and one proportional electrovalve. The hardware developed is based on an embedded microprocessor and provides a low-cost and robust solution. The resulting embedded system has been tested on a spraying system mounted on a manned vehicle. Furthermore, an easy-tuning non-linear PI (Proportional Integral) controller to achieve the desired pressure profile is designed and implemented in the embedded system. Many physical experiments show the best performance of such controller compared with a typical PI controller. Experiments covering the pressure range from 2 to 14 bar obtained a mean error less than 0.3 bar. Summing up, a low-cost automatic pressure-control system is developed, it ensures a uniform decomposition of the liquid sprayed on plants, and it works properly over a wide variable-pressure range.